(untitled) (Archives of Clinical Psychiatry, 2014)
Background : Transcranial direct current stimulation (tDCS) is a novel non-pharmacological intervention being investigated for the treatment of major depressive disorder (MDD). Objective : To perform an updated review of tDCS for MDD. Method : Systematic review in Medline/PubMed and other databases of all clinical studies evaluating the clinical efficacy of tDCS in MDD, from the first date available to December/2013. Results : Out of 55 articles, 24 were included, being 6 open-label studies; 8 randomized, double-blind, sham-controlled trials; 2 follow-up studies; 2 meta-analyses and 6 case reports. We observed an improvement of 20-40% in depressive symptoms, being slightly better in open studies. Five randomized clinical trials displayed positive results. The meta-analyses presented mixed results; although none included the study of Brunoni et al. (2013) that represents almost 50% of the evaluated sample. Open-label studies and case reports also investigated tDCS in bipolar depression, post-stroke depression and employed different parameters of stimulation. Discussion : TDCS is a novel, promising treatment for MDD. Definite evidence from large, ongoing clinical trials will be available in the next years.